Complete revascularization versus culprit-lesion only PCI in patients with NSTEMI and multivessel disease: design and rationale of the randomized COMPLETE-NSTEMI trial - Feistritzer, Hans-Josef; Jobs, Alexander; Zeymer, Uwe; Schneider, Steffen; Lauten, Philipp; Ferenc, Miroslaw; Weferling, Maren; Brinkmann, Regine; Winkler, Sebastian; Landmesser, Ulf; Trippel, Tobias Daniel; Stellbrink, Christoph; et al. (American heart journal, 2025)
Background - Multivessel coronary artery disease (CAD) is present in 30% to 70% of patients presenting with non-ST-segment elevation myocardial infarction (NSTEMI) depending on varying age and risk profiles. In contrast to the STEMI cohort, there is only limited scientific evidence derived from randomized controlled trials directing the general decision for or against complete revascularization in the NSTEMI population. - Primary hypothesis - The COMPLETE-NSTEMI trial aims to investigate whether multivessel percutaneous coronary intervention (PCI) is superior over culprit-lesion only PCI in patients with NSTEMI and multivessel CAD. - Design - COMPLETE-NSTEMI is a prospective, randomized, controlled, multicenter, parallel group, open-label trial. It will enroll 3390 NSTEMI patients with multivessel CAD at 65 to 70 sites in Germany and Austria. Patients will be randomized 1:1 to either complete revascularization with PCI or culprit lesion-only PCI. - Endpoints - The primary efficacy endpoint is a composite of cardiovascular death or rehospitalization for nonfatal myocardial infarction during follow-up. The trial is event-driven and will be stopped as soon as 578 primary endpoint events and a minimal follow-up duration of 12 months for each patient are reached. - Current status - The first patient was enrolled at October 27, 2023. By April 2025, 51 sites have been activated and >500 patients have been randomized. Completion of recruitment is expected for the first half of 2027. The final results of the primary endpoint are expected in 2028. - Outlook - COMPLETE NSTEMI will be the first dedicated trial to answer the question about the optimal revascularization strategy in patients with NSTEMI and multivessel CAD. - Trial registration: ClinicalTrials.gov - NCT05786131
Online verfügbar: 8. April 2025, Artikelversion: 1. Mai 2025
Gesehen am 19.08.2025